Synthesis and Antitumor Activity of Tetrahydroisoquinoline Derivatives - Xue-Ting Feng; Dao-Cai Wang; Hang Song; Shun Yao (Current Topics on Chemistry and Biochemistry Vol. 4, 2022)
The optimized reaction conditions were the reaction time should not exceed 4 h when 1-methylpiperidin-4-one was converted to corresponding a,b-unsaturated ketones, and the DBU was chosen as the most suitable strong base for the reaction of a,b-unsaturated ketones and malononitrile. Then fifteennovel tetrahydroisoquinoline derivatives have been synthesized via the mild synthetic route. The structures of all the compounds were confirmed by 1H NMR spectra, 13C NMR spectra and mass spectra. Their antitumor activities were tested in four human tumour cell lines: human colon carcinoma (HCT116), non-small cell lung cancer (H1975), human lung adenocarcinoma (A549), and human pancreatic cancer (BxPC-3). Among these, compounds 4i and 4j, with GI values of 59.1 and 63.0 percent, respectively, shown substantial growth inhibitory action against the whole examined subpanel tumour cell lines, particularly H1975.